Formation Of Quality Education In The Field Of Pedagogy - Hoshimova Dilnora Samiyevna (Zien Journals, 2023)
This article provides comprehensive information on the use of new technologies in the field of pedagogy and their development in the form of education. Thoughts about the quality of education and its determining factors, as well as the main tasks of teachers-pedagogues in its implementation are highlighted.
Keywords: Professional activity; structure of teacher's professional activity; professional quality